War Memory and Mizoguchi’s Film - Yatagai, Fumie (Tribhuvan University Journal, 2016)
This paper focuses on the Japanese film director called Kenji Mizoguchi who worked not only the making films but gave the caricature impact to the Japanese society. He was touching with the Japanese philosophy and spirit before and after the World War II.He described the common life of the Japanese life, especially tracing on how the women were dis-treated because of the context of the machismo in the public and at home. Also, the women were prohibited to have good education. The Japanese women at that time had a harsh moment to find their identity.For instance, as I experienced the poverty and discriminations just to be a women, Mizoguchi’s film encouraged me and opened a door to the new life.